دور الشمول المالي في تعزيز الاستقرار المصرفي لدول المغرب العربي )الجزائر وتونس (في ظل التكنولوجيا المالية دراسة قياسية خلال الفترة 2006- 2021 - بطيو, نسرين; دحمان, محمد علي (University of Eloued جامعة الوادي, 2022)
This study aims to analyze the relationship between financial inclusion and banking stability in the Arab Maghreb countries (Algeria and Tunisia) based on a sample of 17 commercial banks during the period 2006-2021 using the GMM Panel Dynamic model. The study concluded the following most important results: There is a positive relationship between financial inclusion (FI) and banking stability (Z-score), As well as the existence of the same positive relationship between the profitability of the bank (ROA), the size of the bank (Size), the banking development index (CPS) and banking stability in the Arab Maghreb countries. Whereas market competition index (Lerner) and gross domestic product (GDP) are negative correlated with stability, However, the capital (CAP) did not have any effect on the banking stability during the study period. Accordingly, we conclude that individuals have increased banking awareness and increased their contribution to the banking system, which allowed banks to increase loan grants, which led to an increase in financing the most profitable and productive investments.
The role of financial inclusion in enhancing banking stability in the Arab Maghreb countries (Algeria and Tunisia) In the light of financial technology Standard study during the period 2006-2021
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: Panel Dynamic GMM الشمول المالي، الاستقرار المصرفي، المصارف التجارية، نموذج; Financial Inclusion, Banking Stability, Commercial Banks, GMM Panel Dynamic Model, Arab Maghreb Countries.